Antifungal Activity of TiO2/Ag Nanoparticles under Visible Light Irradiation - Nahzim Rahmat; Endang Tri Wahyuni; Adhitasari Suratman (Universitas Gadjah Mada, 2021)
The doping of TiO2 by Ag(I) from [Ag(S2O3)2]3– contained in radiophotography wastewater by photoreduction method has been performed. TiO2/AgNPs photocatalyst was examined for its activity as an antifungal material for the inhibition of C. albicans in water under visible light irradiation. In the doping process, the weight of TiO2 was varied to obtain TiO2/AgNPs with different amounts of Ag. The TiO2/AgNPs samples were characterized by using FTIR, SRUV, TEM, SEM-EDX, and XRD methods. The antifungal test was carried out by disc diffusion method under visible light irradiation, wherein the amount of Ag-doped on TiO2, the dose of TiO2/AgNPs, and the irradiation time were optimized. The research results indicated that the antifungal activity of TiO2/AgNPs in inhibiting C. albicans has been successfully prepared. The highest inhibition was achieved by using 0.5 g/L of TiO2/AgNPs (I), at 5 h of irradiation time.